Protolichesterinic Acid, Isolated from the Lichen Cetraria islandica, Reduces LRRC8A Expression and Volume‐Sensitive Release of Organic Osmolytes in Human Lung Epithelial Cancer Cells. (9th November 2015) - Thorsteinsdottir, Unnur Arna; Thorsteinsdottir, Margret; Lambert, Ian Henry
Abstract : We have tested the effect of protolichesterinic acid (PA) on the activity of the volume‐sensitive release pathway for the organic osmolyte taurine (VSOAC) and the expression of the leucine‐rich‐repeat‐channel 8A (LRRC8A) protein, which constitutes an essential VSOAC component. Exposing human lung cancer cells (A549) to PA (20 µg/mL, 24 h) reduces LRRC8A protein expression by 25% and taurine release following osmotic cell swelling (320 → 200 mOsm) by 60%. C75 (20 µg/mL, 24 h), a γ‐lactone with a C8 carbon fatty acid chain, reduces VSOAC activity by 30%, i.e. less than PA. Stearic acid (20 µg/mL, 24 h) has no effect on VSOAC. Hence, length of PA's fatty acid chain adds to γ‐lactone's inhibitory action. 5‐Lipoxygenase (5‐LO) activity is essential for swelling‐induced activation of VSOAC. PA has no effect on cellular concentration of leukotrienes (5‐HETE/LTB4 ) under hypotonic conditions, excluding that PA mediated inhibition of VSOAC involves 5‐LO inhibition. A549 cells exposed to the chemotherapeutic drug cisplatin (10 μM, 24 h) reveal signs of apoptosis, i.e. 25% reduction in cell viability as well as 1.3‐, 1.5‐ and 3.3‐fold increase in the expression of LRRC8A, Bax (regulator of apoptosis) and p21 (regulator of cell cycle progression), respectively. PA reduces cell viability by 30% but has no effect on p21/Bax expression. This excludes PA as a pro‐apoptotic drug in A549 cells. Copyright © 2015 John Wiley & Sons, Ltd.